2013
DOI: 10.1111/asj.12131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a non‐forage fiber of red bean hulls on ruminal mat characteristics, chewing activity and milk production in dairy cows

Abstract: The evaluation of red bean hulls (RBH) as a non-forage fiber source on ruminal mat formation, chewing activity and milk production was determined using two experiments. In experiment 1, four non-lactating, rumen-cannulated Holstein cows were offered a control diet of 60.1% forage, and an RBH diet of 51.6% forage and 9.4% RBH. Although the neutral detergent fiber (NDF) intake was higher with the RBH diet than the control diet, the physically effective NDF (peNDF) intake was lower. The rumination period tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Ingestive behaviour in heifers fed diets with increasing levels of babassu cake Analysing the diet x period interaction showed that for each period the time spent ruminating decreased when babassu cake substituted the sugar cane, with a reduction ranging from 0.09667 to 0.13233 minutes per period for each g kg -1 of babassu cake. According to Izumi, Miwa and Ishizuka (2014), by-products that contain high levels of nonforage fi bre can replace both the forage and concentrate in ruminant diets. However, due to its smaller particle size, this type of fi bre is not physically eff ective, which implies a faster rate of passage through the rumen and lower fi bre digestibility, consequently stimulating less rumination (MERTENS, 1997), a fact that was seen in the present study.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Ingestive behaviour in heifers fed diets with increasing levels of babassu cake Analysing the diet x period interaction showed that for each period the time spent ruminating decreased when babassu cake substituted the sugar cane, with a reduction ranging from 0.09667 to 0.13233 minutes per period for each g kg -1 of babassu cake. According to Izumi, Miwa and Ishizuka (2014), by-products that contain high levels of nonforage fi bre can replace both the forage and concentrate in ruminant diets. However, due to its smaller particle size, this type of fi bre is not physically eff ective, which implies a faster rate of passage through the rumen and lower fi bre digestibility, consequently stimulating less rumination (MERTENS, 1997), a fact that was seen in the present study.…”
Section: Variablementioning
confidence: 99%
“…The number of re-chews per bolus (NRB) and the number of re-chews per day (NRC) showed decreasing linear behaviour (P < 0.05; Table 7). This can be explained by the reduction in the bulk to concentrate ratio (B:C) of the feed, and the fact that the cake is a source of non-forage fi bre, which is less physically effective and therefore promotes less re-chewing activity (IZUMI; MIWA; ISHIZUKA, 2014;LI, et al, 2014). As such, the diff erence in the physical characteristics of the diets infl uenced rumination behaviour, with the babassu cake not contributing to increased rumination.…”
Section: Periodmentioning
confidence: 99%
“…Therefore, when using an NFFS as the main fiber source for cows, attention must be paid to the risk of developing subacute ruminal acidosis (SARA) (Humer, Aschenbach et al., ; Krause & Oetzel, ). On the contrary, we measured the physical properties of the ruminal mat using the penetration resistance test in the rumen (Izumi, Miwa, & Ishizuka, ; Izumi & Unno, ) and found that a suitable ruminal mat was formed if grass forage was used in combination with NFFS, even if a large proportion of NFFS was given to dairy cows. However, data regarding the relationship between KP feeding and ruminal mat formation do not exist.…”
Section: Introductionmentioning
confidence: 99%